Toll-like receptor distribution in colonic epithelium and lamina propria is disrupted in HIV viremic, immune success, and failure. (1st May 2020) - McCausland, Marie R.; Cruz-Lebrón, Angélica; Pilch-Cooper, Heather A.; Howell, Scott; Albert, Jeffrey M.; Park, Young S.; Levine, Alan D.
Abstract : Design: Since intestinal immunity and the microbiome are disrupted in HIV disease, we studied the abundance of innate immune sensors, Toll-like receptors (TLRs), in the mucosa of participants with viremia, prior to antiretroviral therapy (ART), immune success (>500 CD4 + T cells/μl after 2 years of ART; suppressed viremia), and immune failure (<350 CD4 + T cells/μl after 2 years of ART; suppressed viremia). We hypothesized that disruption of intestinal TLR abundance and location provides a mechanism behind persistent inflammation. Methods: Immunofluorescence for TLR3, TLR4, and TLR9 on paraffin embedded biopsies from uninfected, viremic, immune success, and immune failure colons was imaged by deconvolution microscopy and quantified with MetaMorph software. Plasma levels of C-reactive protein, IL-6, and intestinal fatty-acid binding protein (I-FABP) were correlated with TLR expression. Results: Viremic participants have significantly higher levels of TLR3 and TLR9 on surface epithelium and in crypts when compared with uninfected controls. TLR3 is further elevated in immune failure and immune success. TLR9 abundance remains elevated in immune failure and is normalized in immune success. TLR9 expression in the crypt and lamina propria positively associates with C-reactive protein and IL-6 and negatively with I-FABP. TLR4 is significantly lower on surface epithelium and higher in crypts in viremic. Its expression in the lamina propria positively correlates with IL-6 and negatively correlates with I-FABP. Conclusion: Mucosal TLR imbalance and deregulation, and the resulting mucosal TLR desensitization and hypervigilance, remain after suppressive ART, in the presence or absence of T-cell recovery, likely contributing to chronic systemic inflammation. Abstract : Supplemental Digital Content is available in the text